Digital Parenting of Children and Adolescents in Digital Era - Aseptianova; Aziz, M. Zalili Aziz; Listini; Sri, Herman; Dewiyeti, Susi (LPPM Undiksha, 2022)
The family is the first environment for children and adolescents so that it has a major influence on the formation of behavior, character, morals, character and education of children. Parenting in the family is the effort of parents to foster and guide children both physically and spiritually from birth to adulthood. This study aims to analyze digital parenting systems for children and adults. The method used in this study is a qualitative and participatory descriptive method, increasing participation and encouraging interest in and commitment to wider participation, encouraging community skills, awareness and attitudes towards parenting and bullying in the digital era. The application of parenting style must be accompanied by several family functions, including biological functions, educational functions, religious functions, protection functions, socialization functions, affection functions, economic functions, creative functions and family status functions. In addition, the way of parenting in the family must be adjusted to the child's developmental stage. Related to the problem of parenting in the family, this is a big task for all parents because at this time there are many conflicts and a lack of sympathy and empathy for children in the association is caused by the parenting style in the family. Therefore, parents should adapt by adjusting their parenting style to the technological developments.